EXPLORING THE INTEGRATIONS OF MALL INTO ENGLISH TEACHING AND LEARNING FOR INDONESIAN EFL STUDENTS IN SECONDARY SCHOOLS - Bramy Biantoro (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2020)
The use of mobile technology for education is on the rise across the world, especially in Indonesia. However, there are concerns in making such an educational revolution as mobile technology may introduce negative side effects to the Indonesian students. Also, only a few studies have discussed the use of mobile technology in Indonesian secondary schools. Those circumstances potentially make many stakeholders doubt the proper implementation of mobile technology-based learning and the possible challenges, especially in English as a foreign language (EFL) classroom. Thus, this paper is aimed to provide theoretical insights into the implementation of mobile-assisted language learning (MALL) for secondary school students in EFL classrooms. A secondary source analysis through systematic review was employed to generate the findings, focusing on MALL and EFL primary research and government documents related to education in secondary schools. Based on the findings, this paper offers an improved teaching and learning approach based on collaborative learning and task-based language teaching (TBLT) to facilitate better implementation and integration of MALL in EFL classrooms. In addition, the findings also show possible challenges during the implementation of MALL in Indonesia for future considerations, such as the technology readiness of EFL stakeholders and teachers’ pedagogical issues related to mobile learning. Lastly, this paper is expected to raise awareness of MALL opportunities and open more paths for more primary research regarding the implementations of MALL in Indonesian EFL classrooms.